PENGARUH PERENCANAAN ANGGARAN, LAPORAN REALISASI ANGGARAN, EVALUASI ANGGARAN DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP AKUNTABILITAS KINERJA PERANGKAT DESA - Zainab Zainab (STIE Mahardhika, 2020)
The purpose of this study is to examine the effect of budget planning, budget realization report, budget evaluation and human resources competencies on the accountability of village official in Gresik district. The sampling technique used purposive sampling with a sample of 312 village employees who worked at least 6 months. The research method used in this study is a quantitative method using statistical packages for the social sciences (SPSS). The result of the analysis use multiple linier regression which show that : 1) budget planning has a positive effect on the accountability of village official performance, 2) the budget realization report has a positive effect on the accountability of village official performance, 3) budget evaluation has a positive effect on the accountability of village apparatus performance, 4) human resources competencies have a positive effect on the accountability of village official performance.